Laparoscopic left lateral hepatectomy : the first case at Thammasat University, Thailand - Chatchai Mingmalairak (Chulalongkorn University, 2007)
Objective: To present the first case of a benign liver tumor, hemangioma, operated with a novel technique oflaparoscopic hepatectomy in Thailand. Method: We report a 48-year-old female patient with chronic epigastric pain. A study of esophagogastroduodenoscopywas normal. Ultrasound examination showed a mass of 6.5 cm in a left lobe of a liver.MRI and RBC scans showed hemangioma. Laparoscopic left lateral hepatectomy was performed. Result: Duration of the operation was 4 hours with approximately 300 cc of blood loss. Post-operative recoverywas good. The patient could return home within 5 days after the operation. There were no complications.Conclusion: Laparoscopic left lateral hepatectomy for benign tumor case may be appropriate.